2021
DOI: 10.3390/cancers13081933
|View full text |Cite
|
Sign up to set email alerts
|

Iatrogenic Ocular Surface Diseases Occurring during and/or after Different Treatments for Ocular Tumours

Abstract: The ocular surface represents a finely regulated system that allows the protection of the eye. It is particularly susceptible to different treatments for intraocular tumours, such as uveal melanoma and conjunctival cancers. Traditionally, the management of ocular tumours depends on the characteristics of the lesion, and is based on a combination of selective surgery, topical chemotherapy, and/or radiotherapy delivered through different mechanisms (e.g., charged-particle radiotherapy or brachytherapy). Possible… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 157 publications
(223 reference statements)
0
1
0
Order By: Relevance
“…Ocular Surface and Ocular adnexa complications Artificial tears, topical corticosteroids, and antibiotic treatment [20] Reconstructive surgery, tarsorrhaphy, or gold weight implantation [20] Contact lenses, autologous serum eye drops, conjunctival flaps, amniotic membrane transplantation, cyanoacrylate gluing [20,21] Lamellar or penetrating keratoplasty [20,21] Scleral Necrosis Observation Artificial lubrication, gels or ointments, like prednisolone acetate 1% [22][23][24][25][26][27][28] Surgical techniques [22][23][24][25][26][27][28] • Tissue glue…”
Section: Complication Available Therapeutic Approachesmentioning
confidence: 99%
“…Ocular Surface and Ocular adnexa complications Artificial tears, topical corticosteroids, and antibiotic treatment [20] Reconstructive surgery, tarsorrhaphy, or gold weight implantation [20] Contact lenses, autologous serum eye drops, conjunctival flaps, amniotic membrane transplantation, cyanoacrylate gluing [20,21] Lamellar or penetrating keratoplasty [20,21] Scleral Necrosis Observation Artificial lubrication, gels or ointments, like prednisolone acetate 1% [22][23][24][25][26][27][28] Surgical techniques [22][23][24][25][26][27][28] • Tissue glue…”
Section: Complication Available Therapeutic Approachesmentioning
confidence: 99%
“…A systematic review of the literature reported a mean risk of recurrence at 52% in cases with positive surgical margins and 11% in cases with negative surgical margins [ 31 ]. Adjuvant therapy, including topical or intralesional chemotherapy, radiotherapy, or plaque brachytherapy, further reduces the persistence of the tumors and the recurrence rates, independent of margin status, but may also cause considerable side effects [ 29 , 32 ]. The application of adjuvant topical interferon alpha-2b in cases with narrow, indeterminate, or negative surgical margins seems to obtain better tumor control than re-excision, incisional biopsy-guided interferon alpha-2b therapy, or empiric interferon alpha-2b treatment as monotherapy [ 31 ].…”
Section: The Conjunctivamentioning
confidence: 99%